IMPLICATIONS OF RETURN ON ASSET (ROA), EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER), AND DEBT TO EQUITY RATIO (DER) TO STOCK PRICE - Elisa Aprianti; Dwi Wahyuningsih (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
The stock price is one of the essential factors that investors must do before investing in a company. The stock price will show the performance of a company. If a company's performance improves, the profits will be even greater. The purpose of investors investing their capital is to be able to provide the highest profit. Several factors can affect stock prices: ROA, EPS, PER, and DER. This study was conducted to determine the effect of ROA, EPS, PER, and DER on stock prices. The gap theory of this research is to add ROA, PER, and DER variables. The population using the food and beverage sub-sector companies for the 2016-2020 period amounted to 34 companies, and the sample obtained was 14 companies using the purposive sampling technique. The analysis in this study uses descriptive statistics, while the hypothesis testing uses multiple linear regression analysis. The results of this study indicate that there is a simultaneous influence between ROA, EPS, PER, and DER on stock prices. Partially, ROA, EPS, and PER positively affect stock prices. Meanwhile, DER does not affect stock prices.